The Effect of Financial Development on Economic Growth Countries ASEAN-4 - Millah, Rizka Lailatul; Wibowo, Wisnu (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2021)
This study aims to determine the effect of financial development on economic growth in ASEAN-4 during 1999-2018. This study uses the regression method and panel approaches using the Fixed Effect Model method. This research uses the FEM quantitative method and uses a stata 13 estimation tool. The panel data regression results in this study indicated that financial development has a positive relationship with economic growth. This is evident from the three financial development proxies, which have a positive correlation with economic growth domestic credit to private sector, money broad variables, market capitalization and degree of openness to reflect the real sector. Keywords: Financial Development, Degree of Openness, Economic GrowthJEL : G2, O11, O16